2017
DOI: 10.1007/s00737-017-0728-7
|View full text |Cite
|
Sign up to set email alerts
|

Associated symptoms of depression: patterns of change during pregnancy

Abstract: Little is known about the natural course of depressive symptoms and associated features throughout pregnancy. We examined the course of some psychological and somatic symptoms in each month of pregnancy in a normative sample. A consecutive, unselected sample of women (N = 374) were interviewed retrospectively at 6 weeks postpartum with the Structured Clinical Interview (DSM-IV). Women were asked whether they had experienced each symptom at any time during pregnancy and the occurrence of the symptom for each mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…There were qualitative differences in core depressive-anxiety symptoms across the peripartum periods as demonstrated in the change of the top central symptoms. This finding adds to the evidence from other studies reporting differences in pre- and post-partum depression profiles with the structured clinical interview ( 81 , 82 ). During pregnancy, the cognitive-affective symptoms were more central.…”
Section: Discussionsupporting
confidence: 80%
“…There were qualitative differences in core depressive-anxiety symptoms across the peripartum periods as demonstrated in the change of the top central symptoms. This finding adds to the evidence from other studies reporting differences in pre- and post-partum depression profiles with the structured clinical interview ( 81 , 82 ). During pregnancy, the cognitive-affective symptoms were more central.…”
Section: Discussionsupporting
confidence: 80%
“…Higher rates of psychological distress among the pregnant women than among their partners have been observed in a previous study . However, it was unexpected that the rates of psychological distress in most of the subscales did not decrease after the information was given among the pregnant women, as previous studies have indicated that the rate of psychological distress is somewhat lower in the middle of the pregnancy . Hypothetically, the result in the present study is related to the higher demands and ideals of pregnant women in Sweden.…”
Section: Discussionsupporting
confidence: 65%
“…Pregnancy is an overwhelming period for many women, characterized by feelings of excitement but also feelings of worry . Worry is a milder form of psychosocial distress and is most common during the beginning stages of pregnancy (when the risk of miscarriage is increased) and in the end of pregnancy (close to childbirth) . Some women get more serious forms of psychosocial distress during pregnancy; in Sweden, about 14% of the pregnant population are diagnosed with depression .…”
Section: Introductionmentioning
confidence: 99%
“…However, no one volunteer subject was diagnosed with anaemia in this present study, according to the hemogram. Despite this being the case after the first pregnancy, 10-15% of women experience mild, moderate, or severe anxiety and depressive symptoms, including feelings of guilt and a lack of appetite and energy to move forward (33). In pregnant women with DS, high plasma levels of inflammatory mediators, such as IL-1b, IL-1, and IL-6, have been observed (34,35).…”
Section: Discussionmentioning
confidence: 99%